Pengembangan Aplikasi Web untuk Pemantauan Konsumsi Energi Listrik - Dion Dwi Andiska; Riska Riska; Yoli Adi Rozzi (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2025)
The need for an efficient electrical energy consumption monitoring system is increasingly urgent in the digital era, especially to overcome power wastage due to the large number of electronic devices used. This research aims to develop a web application. The method used in this research is the experimental method with a system engineering approach, through the user interface. The application was built using PHP, HTML, CSS, and MySQL, and integrated in the XAMPP environment. The test results show that the application is able to display energy data interactively, both in graphical and tabular form, and provide reports in PDF and Excel formats. The system also provides the feature of controlling devices such as lights and fans through the dashboard, thus increasing efficiency and user convenience in managing energy consumption. With its comprehensive features and user-friendly interface, this application is expected to be an effective solution in supporting energy savings.